To evaluate the equation \( y = 5 + 3x - 7 - 2x \) for \( x = 2 \) and \( x = 5 \), follow these steps for each value of \( x \):
- Substitute \( x \) into the equation without simplifying first.
- Evaluate the resulting expression.
For \( x = 2 \):
-
Substitute \( x = 2 \): \[ y = 5 + 3(2) - 7 - 2(2) \]
-
Evaluate: \[ y = 5 + 6 - 7 - 4 \] \[ y = 5 + 6 = 11 \] \[ y = 11 - 7 = 4 \] \[ y = 4 - 4 = 0 \]
So for \( x = 2 \), \( y = 0 \).
For \( x = 5 \):
-
Substitute \( x = 5 \): \[ y = 5 + 3(5) - 7 - 2(5) \]
-
Evaluate: \[ y = 5 + 15 - 7 - 10 \] \[ y = 5 + 15 = 20 \] \[ y = 20 - 7 = 13 \] \[ y = 13 - 10 = 3 \]
So for \( x = 5 \), \( y = 3 \).
Summary of Results:
- For \( x = 2 \), \( y = 0 \)
- For \( x = 5 \), \( y = 3 \)